Self-Reflective Practice, Autoethnography, Storytelling, and Critical Incident Analysis in Exploratory Nursing and Midwifery Research: Facing Social Illnesses and Borderline Personality Disorder - Carlo Lazzari; Elda Nikolou-Walker; Liang Liu (Iranian Journal of Nursing and Midwifery Research)
Background: Hospitals are experiencing a surge in social admissions, saturating beds required for more severe pathologies. Nurses, midwives, and other health care workers can explore this issue by using self-reflective practice to research this phenomenon in depth. This study presents primary qualitative research methods in nursing and midwifery to explore novel hospital presentations. Materials and Methods: The study was conducted from February 2023 to January 2024. We describe the theoretical and practical applications of qualitative inquiry, including Kolb’s self-reflective practice, storytelling, autoethnography, and critical incident analysis, to improve research practice in nursing and generate practice-based evidence and strategies for policy. Results: We crafted and analyzed four prototypical vignettes of people who typically present with social illnesses, epitomized by borderline personality disorder and its impact. By merging patient stories with nurses’ autoethnographies, we can expand insider views and research tools in qualitative research. Conclusions: Qualitative exploratory analysis provided robust and convincing accounts of how nurses and midwives can face and relate to problematic situations in health care. Nurses can use both patients’ narratives and their own to extract salient points and guidance for understanding, theorizing, changing, and policymaking.